In vitro evaluation of microbial D- and L-lactate production as biomarkers of infection - Morovic, Paula; Gonzalez Moreno, Mercedes; Trampuz, Andrej; Karbysheva, Svetlana (Frontiers in Microbiology, 2024)
Mammalian cells produce and metabolize almost exclusively L-lactate, bacterial species have the capacity to produce both D-lactate and L-lactate. The aim of this study was to evaluate the intrinsic production of D-and L-lactate in the most common pathogenic microorganisms causing septic arthritis (SA) and periprosthetic joint infection (PJI) as a potential biomarker for the diagnosis of infection. Following microorganisms were grown according to ATCC culture guides and tested for production of D-and L-lactate: